2022
DOI: 10.3390/en15072601
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Risk Information Disclosures in Non-Financial Corporate Reports of Socially Responsible Energy Companies in Poland

Abstract: Risk management is critical for corporate finance management systems, in addition to corporate social responsibility (CSR) and sustainable development (SD) programs. Stakeholders need risk information to make informed judgments as to their involvement. No studies exist to date concerning disclosure of non-financial and financial risks in corporate annual statements and Polish strategic sector company reports. The authors sought to determine whether energy companies disclosed risks in non-financial annual repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…From the perspective of corporate reputation, Allcott and Sweeney (2017) found that better environmental performance can allow a company to consider the corresponding rights and interests of stakeholders, enhancing their trust in the enterprise and leading to follow-up cooperation, thus improving the enterprise's operating efficiency. Szczepankiewicz et al (2022) put forward the view of negative correlation based on the idea that enhancing an enterprise's environmental report would increase the company's value.…”
Section: Related Workmentioning
confidence: 99%
“…From the perspective of corporate reputation, Allcott and Sweeney (2017) found that better environmental performance can allow a company to consider the corresponding rights and interests of stakeholders, enhancing their trust in the enterprise and leading to follow-up cooperation, thus improving the enterprise's operating efficiency. Szczepankiewicz et al (2022) put forward the view of negative correlation based on the idea that enhancing an enterprise's environmental report would increase the company's value.…”
Section: Related Workmentioning
confidence: 99%
“…Companies focus on presenting awards and other facts that build trust and image (implemented quality systems, anti-corruption practices, adherence to codes of ethics, investment projects, good financial performance, etc.). As a result of stakeholder pressure, the quality of annual reports is expected to improve [99].…”
Section: Situation In the Polish Energy Sectormentioning
confidence: 99%
“…The concept of CSRRs, or IRs, is very closely related to the dialogue between the reporting entity and its stockholders, shareholders, potential investors, and other stakeholder groups. Disclosures related to that dialogue are crucial in the context of assessing the quality of CSRRs and IRs [48][49][50][51][52].…”
Section: Analysis Of Stakeholder Relations Declaration Of Ethics and ...mentioning
confidence: 99%
“…Importantly, however, full-scale audit is not required in the case of non-financial reports. Therefore, subjecting non-financial data to a full-scale audit is a choice rather than a necessity, and depends on the decision of the entity's management [15,[50][51][52]. In most cases, reports are reviewed in order to ascertain (in the form of a statement) whether non-financial data have been disclosed.…”
Section: Analysis Of Stakeholder Relations Declaration Of Ethics and ...mentioning
confidence: 99%
See 1 more Smart Citation